Efektifitas Bimbingan Kelompok Terhadap Minat Belajar Siswa - Ahmad Ghazali; Titin Swatinah; Arifin Nur Budiono (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2021)
Students with low interest in learning are due to several factors such as boredom, association, low learning motivation and physical health. Based on the results of the initial study, it showed that students' interest in learning was low, it was necessary to arrange services to increase students' interest in learning. Students' low interest in learning needs to get help, so it doesn't hinder their developmental tasks. Assistance designed to increase interest in learning is group guidance services. The purpose of the research is to test the effectiveness of group guidance services to increase the learning interest of vocational students in the Computer and Network Engineering major. The sample in this study was 35 students. This study uses an experimental research one group pre test post test design. Collecting data using a questionnaire developed by the researcher. The results showed that the results of the t-table test were: 4.405 > 2.030 at a significance level of 5% with (df = 35 – 1 = 34). The results showed that group guidance services were effective in increasing students' interest in learning. Keywords:Adolescent; Group Conseling; Learn;Vocational High School